A Quantitative Examination of Extreme Facial Pain Expression in Neonates: The Primal Face of Pain across Time. (1st March 2012) - Schiavenato, Martin; von Baeyer, Carl L.
Abstract : Many pain assessment tools for preschool and school-aged children are based on facial expressions of pain. Despite broad use, their metrics are not rooted in the anatomic display of the facial pain expression. We aim to describe quantitatively the patterns of initiation and maintenance of the infant pain expression across an expressive cycle. We evaluated the trajectory of the pain expression of three newborns with the most intense facial display among 63 infants receiving a painful stimulus. A modified "point-pair" system was used to measure movement in key areas across the face by analyzing still pictures from video recording the procedure. Point-pairs were combined into "upper face" and "lower face" variables; duration and intensity of expression were standardized. Intensity and duration of expression varied among infants. Upper and lower face movement rose and overlapped in intensity about 30% into the expression. The expression reached plateau without major change for the duration of the expressive cycle. We conclude that there appears to be a shared pattern in the dynamic trajectory of the pain display among infants expressing extreme intensity. We speculate that these patterns are important in the communication of pain, and their incorporation in facial pain scales may improve current metrics.